Detection of Tax-specific CTLs in lymph nodes of adult T-cell leukemia/lymphoma patients and its association with Foxp3 positivity of regulatory T-cell function - Ichikawa, Ayako (Oncol Lett, 2017)
Human T-cell lymphotropic virus type (HTLV)-1 Tax is a viral protein that has been reported to be important in the proliferation of adult T-cell leukemia/lymphoma (ATLL) cells and to be a target of HTLV-1-specific cytotoxic T lymphocytes (CTLs). However, it is not clear how Tax-specific CTLs behave in lymph nodes of ATLL patients. The present study analyzed the immunostaining of Tax-specific CTLs. Furthermore, ATLL tumor cells are known to be positive for forkhead box P3 (Foxp3)and to have a regulatory T (Treg)-cell-like function. The association between T-reg function and number and activity of Tax-specific CTLs was also investigated. A total of 15 ATLL lymphoma cases with human leukocyte antigen (HLA)-A24, for which Tax has a high affinity, were selected from the files of the Department of Pathology, School of Medicine, Kurume University (Kurume, Japan) using a polymerase chain reaction (PCR) method. Immunostaining was performed for cluster of differentiation (CD) 20, CD3, CD4, CD8, T-cell intracellular antigen-1 and Foxp3 in paraffin sections, and for Tax, interferon γ and HLA-A24 in frozen sections. In addition, the staining of Tax-specific CTLs (HLA-A24-restricted) was analyzed by MHC Dextramer(®) assay in frozen sections. In addition, the messenger RNA expression of Tax and HTLV-1 basic leucine zipper factor were also evaluated by reverse transcription-PCR. Immunohistochemical staining of Tax protein in lymphoma tissue revealed the presence of positive lymphoma cells ranging from 5 to 80%, and immunohistochemical staining of HLA-A24 revealed the presence of positive lymphoma cells ranging from 1 to 95%. The expression of Tax and HLA-A24 was downregulated by viral function. Foxp3, a marker for Treg cells, was expressed in 0–90% of cells. Several cases exhibited Tax-specific CTL (HLA-A24-restricted)-positive cells, and there was an inverse correlation between Tax-specific CTLs and Foxp3. However, neither Tax nor HLA-A24 expression was associated with CTL or Foxp3. Our study indicated the possibility that ATLL cells, which expressed Tax, target of CTL, evade the CTL-mediated immune control by expression of Foxp3 as a Treg function.